Asset management for Kansas counties: the state of practice - Friedrichs, Kevin D. (Kansas State University, 2007)
Asset Management is a relatively new term in the transportation world. It involves a systematic approach to maintaining, upgrading and operating all transportation assets (including infrastructure) cost-effectively. With the Government Accounting Standards Board's Statement 34 (GASB 34) requiring all transportation entities to report all capital assets on their annual reports as well as the development of new software and technologies, Asset Management is becoming easier to implement and quickly becoming an important part of the transportation industry. In Kansas the Department of Transportation has developed and successfully utilized an Asset Management system for all assets including bridges, roadways, drainage structures and signs. Kansas counties however, do not have the funds and personnel to implement and maintain an Asset Management system similar to that of the KDOT. Asset Management systems have only been developed by counties with large populations, but even they have not reached the full potential of the system. This thesis discusses the importance of creating and maintaining an effective Asset Management system. Kansas counties were surveyed and asked a series of questions about their asset management systems, or lack thereof, as well as the successes and failures of these systems. The counties were asked how they prioritize maintenance, what software they are using, and what assets they have inventoried. The results of the questionnaire showed that counties with large populations have shown interest in implementing Asset Management systems and many have worked to implement such a system. Conversely, counties with small populations that do not have the resources have not implemented Asset Management systems. Recommendations for implementing appropriate Asset Management systems are made to counties in the three population ranges: i) less than 5,000, ii) between 5,000 and 50,000, and iii) greater than 50,000. These include software recommendations and creating inventories of all county assets including culverts, signs and pavements.
Keywords: Transportation asset management; Kansas counties; Business Administration, Management (0454); Engineering, Civil (0543); Transportation (0709)